Report on magnetometer geophysical surveys conducted in Hungary, Austria and Croatia in the framework of the Interreg Iron Age Danube project - Czajlik, Zoltán; Kovačević, Saša; Tiefengraber, Georg; Tiefengraber, Susanne; Puszta, Sándor; Bödőcs, András; Rupnik, László; Jáky, András; Novinszki-Groma, Katalin; Holl, Balázs (Dissertationes Archaeologicae, 2018)
-